Weight Loss in Animals and Humans Treated with “Weighlevel”, a Combination of Four Medicinal Plants Used in Traditional Arabic and Islamic Medicine - Said, Omar (Hindawi Publishing Corporation, 2011)
Weighlevel, a mixture of extract of four plants used in traditional Arabic and Islamic medicine as well as in European herbal medicine, was prepared and assessed for its safety and efficacy in weight loss. Leaves of Alchemilla vulgaris, Olea europaea and Mentha longifolia L., as well as seeds of Cuminum cyminum, were used. Cultured human fibroblasts treated with Weighlevel did not exhibit any sign of toxicity as evidenced by lactate dehydrogenase release. These results were confirmed in experimental studies on rats where an LD(50) of 15.3 g kg(−1) was observed. Significant antioxidant properties were seen at very low concentrations of Weighlevel (10 μg ml(−1)) as measured by the lipid peroxidation method. Progressive and significant weight loss was observed in chickens given this mixture weekly for 4 weeks compared with controls. Furthermore, a 3-fold increase in the thermogenesis was seen in rat interscapular brown adipose tissue following exposure to different concentrations of Weighlevel extract as determined by measurement of increased oxygen consumption. In addition, a clinical study was carried out among 80 human volunteers with a body mass index (BMI) of 30.67 ± 2.14 kg m(−2). All 80 subjects were asked to continue their usual diet but to eat only three main meals daily and to take one Weighlevel tablet 30 min before each meal. Fourteen subjects were excluded for not following the protocol, and 66 subjects were all evaluated for efficacy and tolerability of Weighlevel monthly for 3 months. Weighlevel was well tolerated by all subjects, and no side effects were reported. A progressive and significant weight loss was seen in these subjects during the whole study period. Higher levels of weight loss were seen in people with BMI of 25–30 kg m(−2) (overweight) compared to people with BMI >30 kg m(−2) (obese). The BMI was reduced after 3 months from 28.5 ± 1.2 and 32.1 ± 1.8 kg m(−2) to 24.5 ± 1.4 and 27.5 ± 2.2 kg m(−2) in overweight and obese group, respectively. Results indicate safety, tolerability and efficacy of Weighlevel.